Formation of Social Entrepreneurship Character through Buddhist Entrepreneurship Courses: Case Study of Samanera at STAB Kertarajasa - Herman, Herman (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This research aims to explore the impact of Buddhist entrepreneurship courses in forming the social entrepreneurial character of Samanera at STAB Kertarajasa. The research method used is a qualitative approach with in-depth interview techniques and participatory observation of the novices who took the course. The research results show that Buddhist entrepreneurship courses provide a deep understanding of entrepreneurial principles based on Buddhist values, such as karma, seva, and alignment with the common good. This learning helps Samanera to develop social entrepreneurship characters, such as empathy, social sensitivity, collaboration and creativity in creating solutions to social problems. The implication of this research is the importance of integrating religious or spiritual values ​​in entrepreneurship education to form a more holistic and sustainable character in business practice.